Fashion brand internationalization : opportunities and challenges - Jin, Byoungho; Cedrola, Elena, 1965- (Palgrave Macmillan, 2016)
"This book provides a comprehensive view on the internationalization of fashion brands, offering academic and managerial insights into how fashion brands in diverse sizes can build and sustain their businesses in competitive global marketplaces. This book takes a critical look at the global-by-nature fashion industry through a collection of actual cases from multiple countries and cultural backgrounds."--Resumé vydavatele
Keywords: obchodní značky; řízení značky; móda; maloobchod; mezinárodní obchod; marketing; brand name products; brand management; fashion; retail trade; international trade; případové studie; case studies